Culinary preparations based on tamarind (tamarindus Indica L. ) acceptability of major restaurants in Miraflores - Bravo Aranibar, Juan Carlos (2016)
The absence of technical information on properties of tamarind and lack of knowledge of the use of fruit in the preparation of dishes that has as its main ingredient tamarind implies that has no demand in Peruvian cuisine.The first phase tamarind analysis was conducted to know the properties of the nutritional composition determined The highlight in the tamarind fruit is the calcium content of 31.9 mg / 100 g. Acidity is 2.99 g / 100 g expressed in Tartaric acid, these are original sample diluted in 1: 1.11 by fieldwork a survey that determined the level of knowledge of the use of tamarind representatives of culinary preparations made of restaurants located in Miraflores. Were representatives who have recommended us that we should prepare dishes based on tamarind.Then in conjunction with the Chefs of the ULCB dishes I prepared based on the use of tamarind fruit and tasting was conducted for this purpose a second survey that determined which are the dishes that have made most preferred.The results determined that acceptance of this gastronomic proposal the use of tamarind in Peruvian cuisine would be very promising as the dishes prepared were satisfactory, because most respondents liked the taste of tamarind be sweet acid (tartaric acid).